A gene for plant protection: expression of a bean polygalacturonase inhibitor in tobacco confers a strong resistance against Rhizoctonia solani and two oomycetes - Borras-Hidalgo, Orlando; Caprari, Claudio; Hernandez-Estevez, Ingrid; De Lorenzo, Giulia; Cervone, Felice (Frontiers in Plant Science, 2012)
We have tested whether a gene encoding a polygalacturonase-inhibiting protein (PGIP) protects tobacco against a fungal pathogen (Rhizoctonia solani) and two oomycetes (Phytophthora parasitica var. nicotianae and Peronospora hyoscyami f. sp. tabacina). The trials were performed in greenhouse conditions for R. solani and P. parasitica and in the field for P. hyoscyami. Our results show that expression of PGIP is a powerful way of engineering a broad-spectrum disease resistance.